Vector control system for autonomous electric drive - Murtazin, T. E.; Shevchenko, A. A.; Titov, V. G. (Vestnik MGTU, 2023)
The study and development of autonomous electric drive systems are relevant, since currently such systems are widespread especially in the marine and river fleet industries. A simulation model of an autonomous frequency-controlled synchronous electric drive with vector control and active power circuit of an electric motor has been proposed. Simulation results have been presented. The improvement of the control system is aimed at increasing the efficiency and reliability of autonomous electric drives. The implementation of the active power circuit allows one to effectively limit the power consumed from the generator, protecting it from surges that lead to the shutdown of the diesel generator set. The regulation of the active power on the shaft is more appropriate for electric propeller drives than the regulation of the shaft rotation speed. The creation of a unified control system for an autonomous electric drive makes it possible to take into account the mutual influence of parameters of the diesel generator set and the electric motor, including more efficient regulation of the voltage and frequency of the generator in order to maintain the quality of electricity produced at an acceptable level. The integration into a single system will further integrate neural networks as adaptive neural network regulators and Virtual Assistant systems. Modern simulation software makes it possible at the design stage to evaluate the quality of transient processes of currents, speed and torque of the electric motor, as well as the quality of energy parameters of the power supply system. Based on the results obtained, it is possible to form requirements for synchronous machines, for semiconductor elements of the power part and converters. The simulation results confirm the correctness of the adjustment of the control circuits and allow us to talk about the suitability of the developed model for engineering calculations.